10p-2(3p-6)=4(5p-6)-10

Simple and best practice solution for 10p-2(3p-6)=4(5p-6)-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10p-2(3p-6)=4(5p-6)-10 equation:


Simplifying
10p + -2(3p + -6) = 4(5p + -6) + -10

Reorder the terms:
10p + -2(-6 + 3p) = 4(5p + -6) + -10
10p + (-6 * -2 + 3p * -2) = 4(5p + -6) + -10
10p + (12 + -6p) = 4(5p + -6) + -10

Reorder the terms:
12 + 10p + -6p = 4(5p + -6) + -10

Combine like terms: 10p + -6p = 4p
12 + 4p = 4(5p + -6) + -10

Reorder the terms:
12 + 4p = 4(-6 + 5p) + -10
12 + 4p = (-6 * 4 + 5p * 4) + -10
12 + 4p = (-24 + 20p) + -10

Reorder the terms:
12 + 4p = -24 + -10 + 20p

Combine like terms: -24 + -10 = -34
12 + 4p = -34 + 20p

Solving
12 + 4p = -34 + 20p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-20p' to each side of the equation.
12 + 4p + -20p = -34 + 20p + -20p

Combine like terms: 4p + -20p = -16p
12 + -16p = -34 + 20p + -20p

Combine like terms: 20p + -20p = 0
12 + -16p = -34 + 0
12 + -16p = -34

Add '-12' to each side of the equation.
12 + -12 + -16p = -34 + -12

Combine like terms: 12 + -12 = 0
0 + -16p = -34 + -12
-16p = -34 + -12

Combine like terms: -34 + -12 = -46
-16p = -46

Divide each side by '-16'.
p = 2.875

Simplifying
p = 2.875

See similar equations:

| -96-8= | | b+0.08=-1 | | 11x=5x+66 | | 90/h=10 | | Y=4x+ax+6 | | n-55=23 | | 5x+y=168 | | 3x-x=-1 | | 7(6x+3)=21+5x | | 2h+5=9 | | x+78=149 | | z=9/4=2 | | 3x+22-z=162 | | 11*x+4x=5*x+70 | | X+20=16X-48 | | 19x-5=13x-17 | | 1-5/8x8 | | 7x-5+6x+8= | | X+20=2X-6 | | 9/9.1=n/14.8 | | V^2/25=12 | | 2x^2+50=10 | | 16x-12x-21=6x-2x-21 | | 2=6-2z | | b^3-b^2-56b=0 | | 36u=576 | | 4x-8/x-2 | | 2*(10+g)= | | 3x=5(25-7) | | 10x+15y=4290 | | 5X-8=-88 | | 2x-x+10=5x-2 |

Equations solver categories